Thwarted Belongingness and PTSD Symptom Severity among Firefighters: The Role of Emotion Regulation Difficulties. Issue 2 (March 2022) - Leonard, Samuel J.; Vujanovic, Anka A.
The present investigation examined the associations among thwarted belongingness (TB), emotion regulation difficulties (ERD), and posttraumatic stress disorder (PTSD) symptom severity among firefighters. First, the associations of TB and ERD with PTSD symptom severity were evaluated. Second, the indirect effect of TB on PTSD symptom severity through ERD was examined. The sample included 246 trauma-exposed firefighters ( M age = 40.21, SD  = 9.93, 93.1% male) who completed an online questionnaire battery. Results demonstrate significant, positive associations among TB, ERD, and PTSD symptom severity; and an indirect effect of TB on PTSD symptom severity through heightened ERD (β = 0.17; CI [0.08, 0.29]). Alternate indirect effect models were also significant, underscoring the potentially bidirectional associations of these variables. These findings suggest that there is merit in investigating the role of interpersonal factors and ERD among firefighter populations to better understand PTSD symptomatology. Clinical and empirical implications are discussed.